Alcohol dependence and mood disorders - Özpoyraz, N.; Tamam, L.; Karakuş, G. (Journal of Dependence, 2008)
1.163 / 5.000 Alcohol dependence and mood disorders are common illnesses in society, with high social and personal costs. Epidemiological and clinical studies have revealed that the two disorders are interrelated and can coexist throughout life. However, the significance of this relationship remains unclear. This is because the relationship is complex, creating challenges in assessing the present and past. This coexistence is significant for both clinical presentation and public health, and information regarding comorbid conditions becomes crucial. Diagnostic confusion stems from issues with diagnostic criteria and measurement techniques, as well as the complexity of withdrawal and intoxication periods. From a treatment perspective, the focus should be on how to help, rather than determining which is primary or secondary. When both disorders coexist, it is crucial to consider all the patient’s characteristics and address both. A matched treatment approach should aim to achieve a balance between both conditions.